2002
DOI: 10.1007/s00432-002-0394-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA Ploidy and S-phase fraction, but not p53 or NM23-H1 expression, predict outcome in colorectal cancer patients. Result of a 5-year prospective study

Abstract: Our results indicate that DNA aneuploidy and high SPF are associated in CRC with a poor clinical 5-year outcome, while in contrast the prognostic role of TP53 and NM23-H1 expression is still to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Cancer patients exhibited higher serum NDKA levels as expected, in line with the findings reported by our group and others for the protein in tumour tissue compared to normal mucosa using Western blot or immunohistochemistry techniques26282931, as well as for mRNA by Northern blot and RT-PCR242527. Regarding the characteristics of the tumour, we did not find any association between serum NDKA and tumour stage, TNM classification, differentiation grade or location, consistent with that reported by others analysing NDKA expression in tumour tissue2328343536.…”
Section: Discussionsupporting
confidence: 92%
“…Cancer patients exhibited higher serum NDKA levels as expected, in line with the findings reported by our group and others for the protein in tumour tissue compared to normal mucosa using Western blot or immunohistochemistry techniques26282931, as well as for mRNA by Northern blot and RT-PCR242527. Regarding the characteristics of the tumour, we did not find any association between serum NDKA and tumour stage, TNM classification, differentiation grade or location, consistent with that reported by others analysing NDKA expression in tumour tissue2328343536.…”
Section: Discussionsupporting
confidence: 92%
“…To estimate the rate of cell proliferation, the SPF was frequently used in breast cancer, thyroid cancer and oral leukoplakia [21-23]. In colon cancer, high SPF was significantly associated with a poor prognosis [24,25]. We also found that knockdown of CNDP2 reduced cyclin B1 expression, which increased the levels of G2.…”
Section: Discussionmentioning
confidence: 87%
“…A DNA ploidy pattern has been proved to be an important prognostic factor. Diploid tumors conferred a better survival compared with aneuploid tumors (Bazan et al, 2002;Lanza et al, 1998). Tumors of the proximal colon are more frequently diploid than those localized distally to the splenic flexure.…”
Section: Tnm Staging and Prognosismentioning
confidence: 97%